A reforma agrária no Brasil - Jezus, Luis Alberto de (2009)
Such work aims to analyze the reason why the agrarian reform has not been accomplishment in Brazil, from 1964 when the Estatuto da Terra was agreed, which made it legally feasible. Here a review of the literature on this subject is made, including classical and contemporary texts. Also, the conditions in legal and institutional fields are analyzed. The power correlation between ruralistics and landless is evidenced by the action of the involved actors and also, in the evaluation of the main laws which care about the subject. A chapter shows, through the data, the result of such power correlations. The understanding is that the agrarian reform is a fundamental condition for the social differences can reduced the social inequality on the field. It was never made through political reasons, besides bravery absence of the politicians that were afraid to lose ruralistics support, choosing diffuses measures, unable to solve the problem by not promoting the necessaries changes in the agrarian structure of the country